Effects of a positive emotion-based adjuvant psychological therapy in colorectal cancer patients: a pilot study - Cardoso Louro, André; Fernández-Castro, Jordi; Blasco, Tomás (Psicooncología, 2016)
Objective: To examine the effectiveness of an “Enhancing Positive Emotions Procedure” (EPEP) based on positive psychology and cognitive behavioral therapy in relieving distress at the time of adjuvant chemotherapy treatment in colorectal cancer patients (CRC). It is expected that EPEP will increase quality of life and positive affect in CRC patients during chemotherapy treatment intervention and at 1 month follow-up.Method: A group of 24 CRC patients received the EPEP procedure (intervention group), whereas another group of 20 CRC patients did not receive the EPEP (control group). Quality of life (EORTC-QLQC30), and mood (PANAS) were assessed in three moments: prior to enter the study (T1), at the end of the time required to apply the EPEP (T2, 6 weeks after T1), and, at follow-up (T3, one-month after T2). Patient’s assessments of the EPEP (improving in mood states, and significance of the attention received) were assessed with Lickert scales.Results: Insomnia was reduced in the intervention group. Treatment group had better scores on positive affect although there were no significantly differences between groups and over time. There was a trend to better scores at T2 and T3 for the intervention group on global health status, physical, role, and social functioning scales. Patients stated that positive mood was enhanced and that EPEP was an important resource.Conclusions: CRC patients receiving EPEP during chemotherapy believed that this intervention was important. Furthermore, EPEP seems to improve positive affect and quality of life. EPEP has potential benefits, and its implementation to CRC patients should be considered.
Keywords: Colorectal Cancer; psychological Intervention; positive psychology; cognitive-behavioral therapy.